Effects of the Addition of Coconut Shell Oil on Diesel Engine Performance: An Experimental Study - Agung Nugroho; Fajrin Lumela; Rita Dwi Ratnani (Jurnal POLIMESIN, 2022)
Biodiesel is one of the efforts to reduce dependence on fuel oil developed as an environmentally friendly alternative fuel in Indonesia. The addition of coconut shell oil will change the biodiesel properties and engine performance. This study aims to determine the physical properties and performance of fuel in diesel engines due to the addition of coconut shell oil. Several methods were applied to test the physical properties of biodiesel, namely: viscosity, density, cetane number, and calorific value. Meanwhile, the parameters for engine performance testing include torque, power, and specific fuel consumption. Biodiesels used were CS-20 and CS-40 for physical properties tests, and CS-10, CS-15, and CS-20 for engine performance tests. The results found that CS-20 had density of 842 kg/m3, kinematic viscosity of 3.958 mm2/s, cetane number of 62.4, flash point of 305.06°C, and heating value of 43,681.72 kJ/kg. For CS-40, the density was 867 kg/m3, the kinematic viscosity was 1.773 mm2, and the calorific value was 43,390.74 kJ/kg. Based on the results of the diesel engine performance test, the highest torque value was 31.487 Nm on Dexlite at 967 rpm rotation with a mass of 9.51 kg, while the highest power was 4.021 kW on Dexlite at 1752 rpm rotation and torque of 21.919 Nm. The best specific fuel consumption on Dexlite at 3563 rpm rotation used 0.527 liters/kWh. In conclusion, the addition of coconut shell oil to Dexlite reduces energy as the calorific value decreases. Furthermore, it is proven that due to the addition of coconut shell oil, the engine performance is decreasing.